BPJS Kesehatan dalam Perspektif Ekonomi Syariah - Itang Itang (AHKAM : Jurnal Ilmu Syariah, 2015)
This article provides answer to the MUI statements that BPJS is inconsistent with the principles of sharia economics.  First, a solution to avoid Gharar, where participants pay a monthly premium, but it is unclear how much they will receive.Second, the solution to avoid the element of gambling, where financial calculations can be profit or loss. Third, the solution of usury, when claims were received by participants of BPJS greater than the premium paid; therefore, it contains elements of usury and usury Fadl category. Meanwhile, when there is a delay of participants to pay premiums, BPJS establishes fines that is also included nasi'ah usury.DOI: 10.15408/ajis.v15i2.2859